2014
DOI: 10.1002/2013ja019296
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of gravity wave‐induced variations of the OH(8,3), O2(0,1), and O(1S) airglow emissions in the MLT region

Abstract: strongly depends on the rate coefficients in the three-body recombination reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…Yankovsky et al (2016) and Yankovsky et al (2007) reported on differences among O 3 altitude profiles obtained by using the modified kinetic model of Mlynczak et al (1993) and the YM2011 model. Huang and George (2014) on the basis of the photochemical O( 1 S) nightglow model proposed by Hickey et al (1997). The first implementation of O 2 (c) as the O( 1 S) precursor seems to be carried out by Torr et al (1985) on the basis of multiple emissions simultaneously measured from the Spacelab 1 shuttle.…”
Section: The Modified Kinetic Model Of O 2 and O 3 Photolysis Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yankovsky et al (2016) and Yankovsky et al (2007) reported on differences among O 3 altitude profiles obtained by using the modified kinetic model of Mlynczak et al (1993) and the YM2011 model. Huang and George (2014) on the basis of the photochemical O( 1 S) nightglow model proposed by Hickey et al (1997). The first implementation of O 2 (c) as the O( 1 S) precursor seems to be carried out by Torr et al (1985) on the basis of multiple emissions simultaneously measured from the Spacelab 1 shuttle.…”
Section: The Modified Kinetic Model Of O 2 and O 3 Photolysis Productsmentioning
confidence: 99%
“…The O( 1 S) precursor was also assumed to be O 2 (c) by Greer et al (1981) describing in-situ measurements of the ETON campaign and Hickey et al (1997). Huang and George (2014) tuned some rates of quenching reactions on the basis of measurements of the green line emissions at 557.7 nm and the Atmospheric band emissions at 864.5 nm. The vibrational transition 0 − 1 of the electronic transition (Meinel, 1950).…”
Section: The Modified Kinetic Model Of O 2 and O 3 Photolysis Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MACD model consists of the same SFWM and a multiple-airglow chemistry model for O 2 atmospheric bands ((0,0) and (0,1)) and O( 1 S) greenline (Huang and George, 2014). The SFWM simulates a linear, transient, dissipative gravity wave packet (Hickey et al, 2000).…”
Section: The Ohcd and The Macd Modelmentioning
confidence: 99%
“…The results of gravity wave-induced airglow secular variations and fluctuations of these airglow intensities have been published in Huang and George (2014) (HG2014, hereafter). Since both studies use the same numerical models for the investigations, the reader is referred to HG2014 for the methodology and for more detailed model description.…”
Section: Introductionmentioning
confidence: 99%